Approche réglementaire de l'aménagement urbain - Kenniff, Patrick (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
This article is a modified version of a paper delivered at a Conference on the methodology of planning and development held at Trois-Rivières on May 19-20, 1977. Much of municipal control of urban development in Canada today is carried out through the regulatory process. Master plans, zoning, subdivision control and building by-laws are the mainstays of this system. In recent years, the legislatures of most Canadian provinces have incorporated in their respective Planning Acts certain mechanisms designed to improve the municipal regulatory response to the challenge of urban change. These mechanisms often appear to be needlessly complicated, whereas they are in fact designed to circumvent certain difficulties which are inherent in the classical regulatory system. The main objectives which these new mechanisms seek to attain are greater flexibility in the decision-making process, better phasing of development and increased public participation at all levels of planning and decision-making. This article concentrates on the law of the province of Québec, but reference is frequently made to the legislation of other Canadian jurisdictions in order to indicate which avenues might be followed in Québec in order to reform the law governing municipal planning by-laws. After a brief introduction, the second Part of this article is devoted to canvassing the principal legal rules governing municipal planning bylaws: first, with respect to by-laws in general; second, with respect to the extent of the limited powers delegated to municipalities; third, with respect to the adoption and amendment procedure for planning by-laws. The third Part is devoted to a comparative analysis of certain legal mechanisms some of which have become commonplace in other Canadian provinces but which remain largely untried in Quebec. These include minor variances, conditional uses, bonus zoning, site plan by-laws, contract zoning and development control. All of these techniques tend to favour greater flexibility in the administration of land-use planning. Other devices are more useful in seeking to achieve phased development. These include holding by-laws and the requirement that land be serviced before a building permit will issue (the latter technique has been in use in Quebec for many years and is authorized to a limited extent by statute). The article concludes by pointing out that some of the mechanisms canvassed would be of considerable use to town planners in Quebec and should be recognized by statute, preferably in the forthcoming Planning Bill which the present government has promised to introduce in the near future. Town planners should be wary of using them without such legislative sanction, however, because the Canadian courts, with limited exceptions such as in the case of holding by-laws, have struck down attempts by municipalities to step outside the limited statutory authority vested in them.